PENERAPAN PROGRAM MOTIVATIONAL INTERVIEWING MENGGUNAKAN GROUP ART THERAPY PADA GEJALA NEGATIF ORANG DENGAN SKIZOFRENIA (ODS) - Puspitasari, Jessica Amandha; Parwati; Angelia, Cecillia; Wati, Linda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Symptoms in schizophrenia are divided into two, positive symptoms and negative symptoms. Negative symptomsare described as reduced or absent normal function such as withdrawal from social relationships, blunted affect,lack of spontaneity,and flow of conversation. Group art therapy can be given to people with schizophrenia aimedat reducing negative symptoms by using art tools to better understand themselves. In the implementation,motivational interviewing can be used to encourage patients to carry out art therapy programs with motivationfrom within themselves. The implementation of the program was given to the participants with schizophrenia whoare partners in humanitarian projects at Pelita Jiwa Foundation, Tangerang. To see the benefit of the program, apre and post test was conducted using The Scale for the Assessment of Negative Symptoms (SANS) from Andreason(1982). Results from this program shows that there’s a change in the participants regarding the negative symptomsthat exist in each of the participants such as increasing communication skills, expression, activity. According to theresult of the implication, this program can be a method to deal with negative symptoms in schizophrenic patients. ABSTRAKGejala skizofrenia dibagi menjadi dua kategori yaitu gejala positif dan gejala negatif. Gejala negatif dideskripsikansebagai berkurangnya atau ketiadaan fungsi normal seperti menarik diri dari hubungan sosial, afek yang tumpul,kurangnya spontanitas, dan flow of conversation. Penerapan terapi seni kelompok dapat diberikan pada penderitaskizofrenia ditujukan untuk menurunkan gejala negatif dengan menggunakan alat seni untuk lebih memahami dirimereka sendiri. Dalam pelaksanaannya, wawancara motivasi dapat digunakan untuk mendorong pasienmelaksanakan program terapi seni dengan motivasi yang berasal dari dalam diri sendiri. Pelaksanaan programdiberikan pada para partisipan Orang Dengan Skizofrenia (ODS) yang menjadi mitra proyek kemanusiaan diYayasan Pelita Jiwa, Tangerang. Untuk melihat manfaat dari program tersebut, dilakukan pre test dan post testmenggunakan the Scale for the Assessment of Negative Symptoms (SANS) dari Andreason (1982). Hasil daripenerapan program ini menunjukkan bahwa terjadi perubahan pada partisipan mengenai negative symptoms yangada di dalam diri masing-masing partisipan seperti meningkatnya kemampuan berkomunikasi, berekspresi, danberaktivitas. Berdasarkan hasil penerapan,